Oz. The complete first season [videorecording (DVD)] - Fontana, Tom, 1951-; Fontana, Tom, 1951-; Martin, Darnell; Gomez, Nick, 1963-; Segonzac, Jean de; Libman, Leslie; Williams, Larry, 1950-1999; Taylor, Alan, 1965-; Hudson, Ernie; Kinney, Terry; Perrineau, Harold; Walker, Eamonn; et al. (HBO Home Video, 2002)
Welcome to Emerald City, an experimental unit of the Oswald Maximum Security Prison or OZ. As run by Tim McManus and overseen by Warden Leo Glenn, Em City is about prisoner rehabilitation over public retribution. No matter how hardened a criminal or killer, whether you're in for a few years or in for life, you have a role to play. Once inside, choose your friends carefully.